Simulasi Distribusi Suhu Tekanan dan Kecepatan Gas Dalam Pipa Pirolisis Pada Reaktor - Kondensor - Silviana Simbolon; Yeremia Setia (Universitas Medan Area, 2022)
In pyrolysis technology there are various geometric factors that affect the results of pyrolysis, one of which is the connecting pipe between the reactor and the condenser. In this study, simulations were carried out with simscale software to analyze the temperature, pressure and gas velocity in the pyrolysis pipe as the length of the pipe increases. The material used is stainless steel AISI 304. This research begins by determining the dimensions and materials of the pyrolysis pipe, the length of the pipe and the input temperature. The length of the pipe was varied by 1.5 m, 1.75 m and 2 m, with initial temperature variations of 450°C and 550°C, respectively. From the simulation result, Increasing of the pipa’s length then the heat transfer will be close to the optimum condition. So that the output temperature, pressure and velocity will be lower. This happens because the length and diameter of the pipe affect the output. From the simulation results, pipe lengths of 1.5 m, 1.75 m, 2 m with input temperatures of 450°C and 550°C obtained the best results for a pipe length of 2 m with an input temperature of 450°C.